Geochemical Evidence of Ediacaran Phosphate Nodules in the Volyno-Podillya-Moldavia Basin, Ukraine - Sasmaz, Ahmet; Sasmaz, Bilge; Soldatenko, Yevheniia; El Albani, Abderrazak; Zhovinsky, Edward; Kryuchenko, Nataliya (Mdpi, 2023)
The sedimentary basin of Podillya (Volyno-Podillya-Moldavia) is situated in the southwest of the Ukrainian crystalline shield and belongs to the middle part of the Upper Neoproterozoic section of the Moguiliv-Podilska Group. By analyzing the primary oxide, trace, and rare-earth element compositions of the phosphate nodules in the area, this study sought to shed light on the potential precipitation characteristics of the Ediacaran Sea, where phosphate nodules were created. The mean major oxide contents of the nodules were 50.8 wt.% CaO, 34.2 wt.% P2O5, 5.29 wt.% SiO2, 4.77 wt.% LOI, 1.69 wt% Fe2O3, 1.63 wt% Al2O3, and 0.35 wt.% MnO. The average trace element concentrations were 183 ppm Ba, 395 ppm Sr, 13.4 ppm Ni, 32.7 ppm Cr, 62.2 ppm Zn, 764 ppm Y, 16 ppm V, 10.8 ppm As, 75.8 ppm Cu, 84 ppm Pb, 2.1 ppm U, 1.7 ppm Th, and 4.2 ppm Co. The trace element contents were generally low and indicated an assemblage of Cu, Y, As, Cd, and Pb enrichments in comparison to PAAS. The total REE concentrations varied from 1638 ppm to 3602 ppm. The nodules had medium REE (MREE) enrichments and showed similar REE patterns normalized to PAAS. All the nodules had strongly negative Ce, Pr, and Y anomalies and substantially negative Eu anomalies, with four samples being exceptions. These abnormalities suggest that oxic and suboxic sea conditions existed at the time the nodules formed. The extremely high REE concentrations are thought to be the result of REEs being redistributed between the authigenic and detrital phases that were created during the diagenetic equilibration of phosphate with pore water. The genetic hypothesis for phosphate nodule formation states that the nodules were generally formed in oxic and suboxic seawater and were precipitated on slopes in response to a significant upwelling from a deeper basin with abundant organic matter under anoxic/suboxic conditions. The majority of the organic material at the water-sediment interface of the seafloor underwent oxidation before phosphate was released into the pore water of the sediment.
Keywords: phosphate; nodule; ediacaran; REE geochemistry; Podillya Basin; Ukraine